2010
DOI: 10.1038/ejcn.2009.152
|View full text |Cite
|
Sign up to set email alerts
|

Long-term walnut supplementation without dietary advice induces favorable serum lipid changes in free-living individuals

Abstract: Background/Objectives: Walnuts have been shown to reduce serum lipids in short-term well-controlled feeding trials. Little information exists on the effect and sustainability of walnut consumption for longer duration in a free-living situation. Subjects/Methods: A randomized crossover design in which 87 subjects with normal to moderate high plasma total cholesterol were initially assigned to a walnut-supplemented diet or habitual (control) diet for a 6-month period, then switched to the alternate dietary inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 24 publications
2
58
0
1
Order By: Relevance
“…Recent well controlled intervention studies with walnuts [71,72,73,74], almonds [75], hazelnuts [76], pistachios [77], macadamias [78], and peanuts [79] showed LDL-cholesterol reductions ranging from 4% to 11% versus comparator diets, confirming the cholesterol-lowering efficacy of various nut types. A Mediterranean diet supplemented with 30 g of mixed nuts (walnuts, almonds and hazelnuts) per day also showed beneficial effects on the lipid profile compared with advice on a low-fat diet in diabetic and non diabetic participants in the PREDIMED study, a randomized trial of dietary intervention for the primary prevention of cardiovascular disease [80].…”
Section: Nut Feeding Trials With Outcomes On Cardiovascular Risk Fmentioning
confidence: 93%
“…Recent well controlled intervention studies with walnuts [71,72,73,74], almonds [75], hazelnuts [76], pistachios [77], macadamias [78], and peanuts [79] showed LDL-cholesterol reductions ranging from 4% to 11% versus comparator diets, confirming the cholesterol-lowering efficacy of various nut types. A Mediterranean diet supplemented with 30 g of mixed nuts (walnuts, almonds and hazelnuts) per day also showed beneficial effects on the lipid profile compared with advice on a low-fat diet in diabetic and non diabetic participants in the PREDIMED study, a randomized trial of dietary intervention for the primary prevention of cardiovascular disease [80].…”
Section: Nut Feeding Trials With Outcomes On Cardiovascular Risk Fmentioning
confidence: 93%
“…Both epidemiological studies (Fraser et al, 1992;Kushi et al, 1996;Albert et al, 2002;Hu and Willett, 2002) and clinical trials (Kris-Etherton et al, 1999a;Rajaram et al, 2001;Sabate et al, 2003;Gebauer et al, 2008;Griel et al, 2008;Banel and Hu, 2009;Phung et al, 2009;Torabian et al, 2010) have consistently shown that nuts can have an important role in the management of plasma lipids, and reduce CVD morbidity and mortality. The American Heart Association recommends the consumption of nuts as a means of replacing saturated fat with unsaturated fats (Krauss et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, it seems necessary to also present the results with and without control for total energy intake, in addition to the adjustment for body weight. The average total energy consumption for participants on the walnut-supplemented diet and the control diet was 8171 and 7614 kJ, respectively (Torabian et al, 2010). The mean difference between daily total energy intake (557 kJ) during the two diet periods is approximately 50% less than the actual energy intake from walnuts (967 kJ).…”
mentioning
confidence: 93%
“…
In the March 2010 issue of EJCN, Torabian et al (2010) reported the effects of walnut consumption on serum lipids, specifically, total serum cholesterol and low-density lipoprotein (LDL) cholesterol. This randomized crossover trial included 87 subjects who were assigned to a walnutsupplemented group or control group for 6 months and then crossed over to the alternate diet for 6 months.

Although the findings are generally consistent with the results from previous studies (Banel and Hu, 2009), it seems as though this trial could be strengthened with refined analysis and interpretation of the data collected.

…”
mentioning
confidence: 99%
See 1 more Smart Citation